INTER-SENTENTIAL SWITCHING IN ALEXANDER THIAN’S TWITTER ACCOUNT @aMrazing - Yanti, Putu Anita Kusuma; Winarta, Ida Bagus Gde Nova; Marantika, I Made Yogi (J-ELLiT (Journal of English Language, Literature, and Teaching), 2022)
This is a qualitative study that focused on inter-sentential switching found in selected tweets of Alexander Thian’s Twitter account @aMrazing. The data being collected by documentation process. The objectives of the study are to observed the reasons of inter-sentential switching and find which reason is the dominant one. A theory proposed by Hoffman (1991) was used as a guidance to achieve the objectives. The final findings concluded that the seven reasons from the theory are completely found in the data. Also, Alexander Thian’s intention of clarifying the speech content for his followers on Twitter as interlocutors is the most prominent reason with 38% occurrences of total data. The particular reason found in 19 out of 50 data. Among the reasons, the least of all is the reason for quoting somebody else which only has 4% occurrences.